Effectiveness of The Board of Commissioners As A Moderator Between Green Intellectual Capital And Firm Value - Satria, Adam Muhamad; Hernawati, Erna (Dinasti Publisher, 2024)
The amount that investors are willing to pay in monetary terms is known as the firm value. A corporation's environment-based approach can increasingly firm value. This article's goal to ascertain how green intellectual capital affects firm value with supervisory efficiency by the board of commissioners. This reasearch using quantitative approach with secondary. utilizing moderated regression analysis. Purposive sampling was used to sample 104 companies in the consuming sector's manufacturing companies. The study's conclusions show that green human capital significantly increases firm value. There is no discernible impact of green relational capital or green structural capital on firm value. The effectiveness of the board of commissioners strengthens the relationship between green human capital and relational capital on firm value. Supervision from the board of commissioners can increase the trust of many parties related to environmentally based investments. The effectiveness of the board of commissioners does not moderate the relationship between green structural capital and firm value.